"Coming to our Senses: Historicizing Sound and Noise in the Middle East". Issue 4 (19th March 2013) - Fahmy, Ziad
Abstract This speculative essay is a call for further research and the beginning of a long overdue conversation among historians of the Middle East about the importance of sounds and soundscapes in studying history. In the process, I will suggest some research strategies for uncovering the sounds and noises of the past – especially before the introduction of recording technologies. All the while, I hope to encourage more multidisciplinary conversations by Middle East historians with other scholarly disciplines that examine sound and listening.